Assessment of real and inevitable losses in water supply systems (Proceedings of Faculty of Civil Engineering, 2025)
Water losses in water supply systems cause significant economic and environmental damage. In addition to increasing the costs of drinking water distribution, they also negatively affect water resources, which is particularly critical in areas with limited water availability. Despite efforts to reduce them, water losses in the Republic of Croatia still account for a significant share of total consumption, averaging up to 50% of abstracted water volumes. The assessment of water losses is based on specific performance indicators of the water utility infrastructure, among which the Infrastructure Leakage Index (ILI), proposed by the International Water Association, is particularly important. ILI is defined as the ratio of current real losses to unavoidable losses. This paper presents the theoretical basis for the assessment of the ILI indicator, with emphasis on the key parameters influencing it (real and unavoidable losses, pipeline length, average system pressure, and the number of consumers). A practical example of ILI assessment was also provided, based on a hydraulic model of a selected District Metered Area (DMA). Using the EPANET software, pressures within the given DMA zone were modeled, and the obtained data were used to estimate real and unavoidable water losses. The analysis identified areas within the DMA zone that require the implementation of measures to reduce water losses and improve the operational efficiency of the system. It was concluded that reducing the ILI indicator to a target value can only be achieved through the iterative application of numerical analyses and field measurements.
Keywords: Water supply systems; losses; ILI indicator; DMA zone; EPANET